PENGGUNAAN MODEL COOPERATIVE LEARNING TIPE MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR IPS DI KELAS V SD - Yuliani, . (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract The problem of this research is by using make a match can improve the social science students learning outcome? The goal of this research is by using make a match can improve the social student learning outcome at the fifth grader elementary student at SDN 09 Southeast Pontianak. The method which use in this research is descriftive method and the form is classroom action research, and the kind of the research is collaborative. The resource of this research is teacher and the student of fifth grade at SDN 09 Souteast Pontianak. The sample was 32 student. The technique of collecting the data is direct observation and students learning outcomes sheet. The research was conducted in three cycles, with the result the teacherâ€™s ability in preparing the lesson at the first cycle is 3,25 an the second cycle is 3,57 and the third cycle is 3,76. The teacherâ€™s ability in implementary the lesson at the first cycle is 3,29 and at the second cycle is 3,67 an the third cycle is 3,71. The learning outcome of the student at the first cycle is 67,18 and the second cycle is 3,75 and the third cycle is 85,31.The learning outcome of the student at the first cycle is 67,18 and the second cycle is 83,25 an the third cycle is 85,31. This thing proved that by using make a match model can improve the social science learning outcome at the fifth grade student at SDN 09 Southeast Pontianak. Â Keyword: Cooperative Learning, Make A Match, Social Science